2015
DOI: 10.3221/igf-esis.34.36
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defect length on rolling contact fatigue crack propagation in high strength steel

Abstract: The objective of the present paper is to clarify the effect of defect length in depth direction on rolling contact fatigue (RCF) crack propagation in high strength steel. RCF test and synchrotron radiation micro computed tomography (SR micro CT) imaging were conducted. In the case of the defect with the 15 ?m diameter, flaking life decreased with increasing defect length. In a comparison of the CT image and the SEM view, the shapes of defects and the locations of the horizontal cracks were almost the same resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The specimen was quenched at 1103 K for 0.5 h and tempered at 453 K for 2 h. The average dimensions of MnS inclusions were 28.2 μm in length and 12.0 μm in diameter. Although those are much larger than the inclusions containing in actual bearings, the flaking mechanism is considered to be similar because the stress concentration is similar for similar shape inclusions 57 . Specimens with an artificial hole with a diameter of 15 μm and a depth of 200 μm, which was introduced by electrodischarge machining and simulates a vertical inclusion, were employed only for a preliminary test for the comparison of crack propagation behavior between rotating contact and reciprocal contact; other specimens had no artificial hole.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specimen was quenched at 1103 K for 0.5 h and tempered at 453 K for 2 h. The average dimensions of MnS inclusions were 28.2 μm in length and 12.0 μm in diameter. Although those are much larger than the inclusions containing in actual bearings, the flaking mechanism is considered to be similar because the stress concentration is similar for similar shape inclusions 57 . Specimens with an artificial hole with a diameter of 15 μm and a depth of 200 μm, which was introduced by electrodischarge machining and simulates a vertical inclusion, were employed only for a preliminary test for the comparison of crack propagation behavior between rotating contact and reciprocal contact; other specimens had no artificial hole.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of RCF crack initiation and propagation was discussed referring to the results obtained by SR‐μCT and FE analysis 24,55–57 . The introduction of the circular hole led to higher tensile residual stress than that in the same region without the hole.…”
Section: Introductionmentioning
confidence: 99%
“…We first performed RCF tests on specimens with EDM‐machined circular holes simulating stringer‐shaped inclusions of various diameters and depths, and we then observed the crack initiation morphology by SR‐μCT of the specimens cut out including the holes 28 . Next, the RCF test was interrupted, and laminography, which is used to observe crack initiation and propagation behavior sequentially, was performed using ultrabright synchrotron radiation X‐rays 57–62 . The results of RCF tests on plate specimens containing stringer‐shaped MnS inclusions revealed that the cracks originated from inclusions on the specimen surface and propagated into the interior, forming additional cracks parallel to the surface from around the tips of the original cracks, rather than propagating from the interior toward the surface and forming flaking, as previously believed.…”
Section: Introductionmentioning
confidence: 99%